Cannabinoids and the endocannabinoid system in immunotherapy: helpful or harmful? - Sarsembayeva, Arailym; Schicho, Rudolf (Frontiers in Oncology, 2023)
Numerous studies in various cancer models have demonstrated that ingredients of cannabis can influence tumor growth through the endocannabinoid system (ECS), a network of molecules (mediators, receptors, transporters, enzymes) that maintains homeostasis and protection in many tissues. The main constituents of the ECS are the classical cannabinoid (CB) receptors, such as CB1 and CB2, their endogenous ligands (endocannabinoids), and the endocannabinoids’ synthesizing and degrading enzymes. The role of the ECS in cancer is still unclear and its effects often depend on the tumor entity and the expression levels of CB receptors. Many studies have highlighted the tumor cell-killing potential of CB1 agonists. However, cannabis is also known as an immunosuppressant and some data suggest that the use of cannabis during immunotherapy worsens treatment outcomes in cancer patients. CB receptors are widely present in immune cells, and together with monoacylglycerol lipase, the 2-arachidonoylglycerol degrading enzyme, they could be critically involved in the regulation of the immune cell profile of the tumor microenvironment (TME), and hence in tumor progression. So far, data on the impact of the ECS in the immune-TME are still vague. In this review, we discuss the current understanding of the ECS on immunoregulation during tumor growth, and how it might affect the outcome of cancer immunotherapy.